Design and Development of An E-Voting Model for Village Head Elections Based on Android - Lestri Yanti; Ardi Wijaya; Yovi Apridiyansyah; Pahrizal Pahrizal (Penerbit Jurnal Indonesia, 2023)
Voting or voting in a democratic country is an important part of the means of selecting leaders. Village head elections are generally still carried out conventionally, elections still use paper to elect village heads (Kades) which are carried out by punching one of the candidate images. The problem that arises is that voters must come to the polling place in order to be able to collect data and vote, for Citizens who cannot attend the polling place or do not exercise their right to vote will add to the data on the abstentions list that is present at the election. In village head elections (Pilkades) the vote counting process is still done manually so it takes quite a long time. This study aims to build an e-voting simulation system which is expected to provide knowledge of technological developments in the field of general elections. This system development method uses Waterfall. Furthermore, if you have obtained the results, you will test the system that was built by testing it with the black box testing method to see in terms of functionality all features are running smoothly or not. The results of testing the E-voting application for village head elections show that the system can run well and has been implemented so that it can be used on Android-based smartphone devices.